Understanding the well-being of residents in Chinese Continuing Care Retirement Communities—a case of Shanghai - Wang, Xuechun; Xia, Bo; Skitmore, Martin; Volz, Kristy; Shu, Bodi (Frontiers in Public Health, 2024)
Introduction China is one of the world’s fastest-aging countries. Continuing Care Retirement Communities (CCRCs) have emerged as a viable option for accommodating and serving older adults. However, Chinese CCRCs are still in the early stages, and comprehensive research on resident well-being is still deficient. The study aims to assess how well residents in CCRCs are faring in terms of their psychological and physical health, considering China’s aging population and changing societal structures. Methods After a thorough literature review to pinpoint relevant well-being measures in psychological and physical health, the study implemented a survey to capture residents’ experiences and perceptions, and subsequently analyzed how well-being correlates with demographic characteristics. Results and discussion The results show that while Chinese CCRCs can enhance residents’ well-being through personalized care and social activities, challenges such as psychological distress and declining physical health remain. Demographic factors, including living situation and length of stay, also affect residents’ well-being. The study emphasizes the importance of ongoing research and evaluation to guide evidence-based practices and improve CCRCs continuously. Overall, it offers a comprehensive analysis of the wellbeing of Chinese CCRCs residents, shedding light on both psychological and physical health aspects and providing valuable insights for enhancing CCRCs design, implementation, and evaluation in China and elsewhere.